2018
DOI: 10.1111/clr.13339
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐implant tissue healing at implants with different designs and placement protocols: An experimental study in dogs

Abstract: Bone remodeling occurred within the early healing phase. During the full 20 weeks of observation, PS-implants demonstrated significantly less crestal bone loss compared to PM-implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
0
7
0
3
Order By: Relevance
“…Thus, one should expect that placement of the implant platform will be at a subcrestal position for at least one surface when treating patients for single tooth replacements. The effect of subcrestal placement on peri‐implant bone alterations for the specific implant system has been evaluated in both animal (Fetner et al, ; Oskarsson, Otsuki, Welander, & Abrahamsson, ; Weng et al, ) and clinical studies (Koutouzis et al; Froum et al, ). In general, in those studies, it was observed that subcrestal implant placement can induce greater bone remodeling above the implant platform.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, one should expect that placement of the implant platform will be at a subcrestal position for at least one surface when treating patients for single tooth replacements. The effect of subcrestal placement on peri‐implant bone alterations for the specific implant system has been evaluated in both animal (Fetner et al, ; Oskarsson, Otsuki, Welander, & Abrahamsson, ; Weng et al, ) and clinical studies (Koutouzis et al; Froum et al, ). In general, in those studies, it was observed that subcrestal implant placement can induce greater bone remodeling above the implant platform.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been described in the current study for the buccal aspect of the study implants. Buccal mucosal recession was observed from the time of implant installation to final crown delivery has been evaluated in both animal (Fetner et al, 2015;Oskarsson, Otsuki, Welander, & Abrahamsson, 2018;Weng et al, 2008) and clinical studies Froum et al, 2018). In general, in those studies, it was observed that subcrestal implant placement can induce greater bone remodeling above the implant platform.…”
Section: Discussionmentioning
confidence: 99%
“…Para valorar la eficacia de los implantes con plataforma reducida o platform switching se han realizado estudios histológicos e histomorfométricos en animales, especialmente en perros Beagle para analizar el grado de oseointegración y el nivel de los tejidos duros y blandos periimplantarios (Figura 2) [27][28][29][30][31][32][33] .…”
Section: Estudios Experimentales De La Plataforma Reducida En Animalesunclassified
“…Oscarsson y cols 31 llevaron a cabo otra investigación en la que colocaron un total de 48 implantes en 6 hembras de Labrador para estudiar los tejidos blandos y duros alrededor de los implantes con plataforma reducida y con plataforma convencional, colocados en una posición crestal o subcrestal y mantenidos con o sin higiene bucal durante 5 meses. La preservación del nivel óseo fue similar independientemente de la colocación crestal o subcrestal de los implantes con cambio de plataforma hasta 5 meses después de la colocación.…”
Section: Estudios Experimentales De La Plataforma Reducida En Animalesunclassified
“…(7)(8)(9) Advantages of platform switching concept over platform matching (PM) implant seems to include; distribution of load between the abutment and the implant, controlling circumferential bone loss around dental implants, increase the thickness of soft tissue collar around the abutment, preventing apical migration of soft tissue, preserving the integrity and location of the papilla on the bony ring and prompting bloodstream in the bone, especially with the small distance between the implants. (10)(11)(12) Additional clinical trials are required to affirm the benefits of PS as asserted by systematic reviews. Heterogeneous factors may affect the outcomes of PS study; implant insertion level, implant microstructure, the size of the implant and implant design.…”
Section: Introductionmentioning
confidence: 99%